Teachers' perceptions about task-based language teaching: a case study of secondary schools at a district in Pakistan - Hayat Ullah; Rose Patsy Tibok; Wong, Jane Kon Ling (2020)
Task-based language teaching is an acceptable method of teaching learning process proposed by Prhabu in 1987 and has been effectively used since then. However, in order to see the applicability of this method in English learning in the Pakistani context, research is needed to know the perceptions of teachers’ teaching at secondary school level in the government schools of District Mardan, Khyber Pakhtunkhwa, Pakistan. The objectives of this research paper are to explore the general perceptions of the English teachers, the effectiveness of TBLT and their suggestions. In order to achieve the objectives of this study mixed questionnaire was administered to 16 English teachers at secondary schools in the urban area of district Mardan. Data were analyzed using mean, mode, standard deviation and frequency. It was found that TBLT is more effective than a traditional language teaching methodology. The study highly recommended the use of TBLT for English teachers teaching at secondary school in Pakistan students for English language learning skills.